MEDIA KOMIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 1 SUKABUMI BANDAR LAMPUNG - Yoga Anjas Pratama (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2018)
This article discusses the use of comic media in improving student learning of class V in learning Islamic Religious Education in SDN 1 Sukabumi Bandar Lampung. Comic media is media in cartoon form expressing character and presented in story form. Comic media is a simple media, informative, educative and can increase the value of learning. Based on preliminary observation, it is known that the learning outcomes of learners in the learning of Islamic religious education are still low. This is caused by the lack of use of comic media in learning for it as a follow-up effort then conducted research on the use of comic media to improve student learning outcomes. This research is a classroom action research (PTK) conducted in two cycles. From the research conducted known that the use of comic media can improve learning outcomes of learners. This is based on learning outcomes obtained learners that at the time of pre-test obtained the number of classical mastery as much as 40% which increased to 71% in cycle I and increased again to 92% in cycle II.